The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1146/annurev.pharmtox.42.082701.145401
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Psychology: Roles for the ERK MAP Kinase Cascade in Memory

Abstract: In this review we describe an emerging understanding of the roles of the Extracellular-signal regulated kinase/mitogen-activated protein kinase (ERK/MAPK) cascade in learning and memory. We begin by describing several behavioral memory paradigms and review data implicating ERK as an essential component of the signal transduction mechanisms subserving these processes. We then describe evidence implicating ERK as a critical player in synaptic and neuronal plasticity-a cellular role likely to underlie ERK's behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
393
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 548 publications
(409 citation statements)
references
References 146 publications
13
393
0
3
Order By: Relevance
“…Recent studies have shown that inhibition of hippocampal MEK/ERK signaling impairs synaptic plasticity as well as long-term memory formation (Davis et al, 2000;Kelly et al, 2003;Adams and Sweatt, 2002). Consistent with this, in the present study, direct infusion of U0126, a specific MEK inhibitor (Hotokezaka et al, 2002), into the CA1 subregion of the hippocampus, also impaired reference memory in the Rats were treated with U0126 and rolipram 24 h after initial training; test data shown were obtained 24 and 48 h posttraining.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Recent studies have shown that inhibition of hippocampal MEK/ERK signaling impairs synaptic plasticity as well as long-term memory formation (Davis et al, 2000;Kelly et al, 2003;Adams and Sweatt, 2002). Consistent with this, in the present study, direct infusion of U0126, a specific MEK inhibitor (Hotokezaka et al, 2002), into the CA1 subregion of the hippocampus, also impaired reference memory in the Rats were treated with U0126 and rolipram 24 h after initial training; test data shown were obtained 24 and 48 h posttraining.…”
Section: Discussionsupporting
confidence: 90%
“…Inhibition of cAMP/PKA signaling impairs memory, especially long-term memory (Koh et al, 2002); stimulation of this pathway enhances memory (Barad et al, 1998;. Similar to cAMP signaling, the MEK/mitogen-activated protein kinase (MAPK, ERK) pathway also has been shown to be involved in the mediation of synaptic plasticity and memory (Adams and Sweatt, 2002;Schafe et al, 2000;Sharma et al, 2003). Activation of ERK signaling enhances the induction of longterm-synaptic facilitation as well as long-term memory (Purcell et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The Ras-controlled Raf-MEK-ERK protein kinase signaling cascade is known to play a critical role in the development of neuronal plasticity Sweatt, 1996, 1997;Martin et al, 1997) and long-term memory formation (Atkins et al, 1998;Orban et al, 1999;Adams and Sweatt, 2002). Changes in ERK signaling have also been associated with drug-dependent behavioral plasticity (Pierce et al, 1999;Valjent et al, 2000;Mazzucchelli et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…For example, pharmacological inhibition of MEK, the upstream activator of the two major ERK isoforms in the brain (ERK1 and ERK2), prevents both hippocampus-and amygdala-dependent memory formation (Atkins et al, 1998;Schafe et al, 1999;Adams and Sweatt, 2002). Pharmacological blockade of the Raf-MEK-ERK cascade also attenuates the development of a conditioned place preference to cocaine, amphetamine or MDMA (Valjent et al, 2000;Salzmann et al, 2003;Gerdjikov et al, 2004) and appears to modulate the development of psychomotor sensitization to cocaine (Pierce et al, 1999;Valjent et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…32 Thinking along these lines, improvement in cognition and in learning processes has been closely related to activation of MAP kinases. 60 These second messengers, in turn, are known to be stimulated by EPO in neurons. 27,[61][62][63] Another novel finding was the effect of EPO treatment on serum levels of the glial damage marker, S100B.…”
Section: H Ehrenreich Et Almentioning
confidence: 99%